FManajemen Retensi Dokumen Rekam Medis Nonaktif Kasus Tb Paru Di Puskesmas Halmahera Kota Semarang Tahun 2019 - Nanda Dhea Aparanita; Retno Astuti Setijaningsih (Dian Nuswantoro Semarang, 2020)
Medical records at non-hospital health care facilities are stored for at least 2 years after the last date of treatment. Halmahera Primary Health Care (PHC) has never done retention or destruction of medical record documents for pulmonary TB cases. The study aims to determine the factors that were obstacles in the retention of pulmonary TB cases at Halmahera PHC. This research is descriptive qualitative research with cross sectional approach. Data collection by observation and interviews. The subjects of this study were 5 filing officers. The object of this study were medical record documents of pulmonary TB patients, the policy of medical record document retention for pulmonary TB cases, the standard of medical record document retention for pulmonary TB cases. Based on the results of the study, 3 out of 5 filing staff understood retention of medical record documents in general, The filing storage systems was centralized but medical record documents for pulmonary TB cases were not included into the family folder, there were no policies and standards regarding retention of medical record documents for pulmonary TB cases, there is no facilities for medical record document retention for pulmonary TB cases. The obstacle in the implementation of medical record document retention for pulmonary TB cases were the unavailability of retention facilities, no schedule for archive retention, no place to store the inactive medical record documents, and excessive staff workload. Suggestions, The PHC need to make standards about document retention for pulmonary TB cases, provide information and technical guidance to filing staff about medical record document retention.Keywords: filing staff knowledge, storage system, retention standard Literature : 15 (2001 – 2020)